Aplicativo multimedia para mejorar la comprensión oral y escrita en niños de segundo año de básica elemental de la Unidad Educativa Fiscomisional Don Bosco, Macas - Barragán Bósquez, Segunda Gloria (2022)
The purpose of this research project is to determine how the multimedia application affects oral and written comprehension in second-year elementary school children of the Don Bosco Fiscomisional Educational Unit, Macas. The study comprises a document that has been developed following a sequential structure starting with the search for information and the identification of existing weaknesses and strengths at the level of study mentioned; then, with the theoretical contributions, expand knowledge and thus propose a proposal as an alternative solution. The importance of including a multimedia application that helps oral and written comprehension is identified in the study, as a reference to the importance that the population gives to this type of resource. The project makes use of types of research such as: descriptive, bibliographic and field; The data collection technique applied is a survey of second grade parents, where clear and precise results were obtained that led to the development of the multimedia application "Funny Letters", whose purpose will be to strengthen oral and written comprehension. The document is finalized with the development of the proposal and the design of the proposed program.